Study of the association between gait variability and gene expressions in a mouse model of transient focal ischemic stroke. (2nd January 2020) - Chen, Mei; Lyu, Hao; Li, Tu; Su, Xian Wei; Leung, Chi Kwan; Xiong, Mark Zhi Qiang; Poon, Wai Sang; Cai, Ye-Feng; Lu, Gang; Chan, Wai-Yee; Wang, Li-Xin
Abstract: Purpose: Gait variability analysis has been clinically adopted to characterize the presentation of various neurological diseases. However, literature and practice lack a comprehensive murine model assessment of the gait deficits that result from transient focal ischemic stroke. Further, correlations between gait parameters and the gene expression profiles associated with brain ischemia have yet to be identified. This study quantitatively assesses gait deficits through a murine model of transient focal cerebral ischemia on day 7 to determine associations between gait deficits and ischemia-related gene expressions. Methods : A total of 182 dynamic and static gait parameters from the transient middle cerebral artery occlusion (MCAO) murine model for simulating human transient focal ischemic stroke on day 7 were measured using the CatWalk system. Pearson's correlation analysis and genes associated with ischemia were identified from the existing literature to aid the investigation of the relationship between gait variability and gene expression profiles. Results: Thirty-nine gait parameters and the mRNA expression levels of four of the eight ischemia-associated genes exhibited more significant change in the MCAO models ( p < 0.005) on day 7. Twenty-six gait parameters exhibited strong correlations with four ischemia-associated genes. Conclusion: This examination of gait variability and the strong correlation to the gene expression profiles associated with transient focal brain ischemia on day 7 provides a quantitative and reliable assessment of the MCAO model's motor performance. This research provides valuable insights into the study of disease progression and offers novel therapeutic interventions in the murine modeling of ischemic stroke.